Chemically synthesized and cross-linked PDMS as versatile alignment medium for organic compounds. Issue 1 (2nd December 2016) - Moskalenko, Yulia E.; Bagutski, Viktor; Thiele, Christina M.
Abstract : Synthesis of PDMS gels with controlled amount of cross-linker opens up the opportunity for tuning of alignment media for RDC structure elucidation of organic molecules and mixtures of their isomers. Abstract : A useful procedure for the preparation of chemically synthesized and cross-linked polydimethylsiloxane (PDMS) gels is presented, which does not require β-irradiation for cross-linking. NMR spectra of high quality are obtained, such that even mixtures of compounds exhibiting similar NMR spectra like interconverting stereoisomers can be investigated in the residual dipolar coupling (RDC) approach of organic structure determination.